PRODUKSI INULINASE DARI UMBI DAHLIA (Dahlia variabilis) OLEH Pichia manshurica DUCC Y-015 DENGAN VARIASI WAKTU INKUBASI DAN KONSENTRASI GLUKOSA SEBAGAI SUMBER KARBON TAMBAHAN - Fathika Fitrania; MG. Isworo Rukmi; w wijanarka (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2018)
The production of fructose from inulin by inulinase would only take one stage enzimatis reaction and yielding 95% fructose. Inulin obtained from the dahlia tubers and inulinase produced by Pichia manshurica DUCC Y-015. The production of inulinase (E.C 3.2.1.7) can be influenced by the presence of glucose as additional carbon source. The purpose of this research is to analyze influence of variation glucose concentration and incubation time to production inulinase P. manshurica DUCC Y-015 in dahlia tubers substrate. Measurement of production enzyme covering activity inulinase and activity invertase. Both analyzed by DNS method and determined based on 1 µmole fructose resulting. The design used in this research were Randomized Factorial Block Design ( RAFBD ). Factor I in the form of glucose concentration 0% (G0); 0.25% (G1); 0.5% (G2) and factor II were incubation time 6 hours (T6), 12 hours (T12), and 18 hours (T18) with repetition 3 times. The data obtained were analyzed by ANOVA method. The result showed variation of glucose concentration and incubation time difference had no significant effect on production of inulinase from P. manshurica DUCC Y-015. The highest production of the inulinase was demonstrated by treatment G1T12 with 0,25% glucose and incubation time 12 hours with value of the activity of inulinase as much as 0,574 IU/mL. Keywords : Dahlia tubers, Glucose, Inulinase, Incubation time, Pichia manshurica DUCC Y-015,